Prevalence of bullying in fourth, fifth, and sixth grades for children with and without mild disabilities: A comparison study - Howell, Erica; Flores, Catherine (Wydawnictwo Naukowe UAM, 2014)
This investigation examined perceptions of bullying for students with (n = 15) and without (n = 60) mild disabilities in grades 4th, 5th, and 6th in a school district in the state of California in the United States of America. Specifically, the following questions were investigated: 1) Do students with disabilities perceive a higher prevalence of being bullied than students without disabilities? 2) When different disability groups are compared, how do they rate the amount of bullying experienced? 3) How do students who have been bullied rate school enjoyment when compared to students who have not been bullied? and 4) Do significant differences emerge between students who have and have not been bullied on their ratings of the amount of friends? Notably, no significant differences emerged between the groups. These findings are striking in light of past research. The discussion will explore implications related to the study findings, including potential protective mechanisms that reduced the participants’ exposure to bullying.
Keywords: bullying; disability; mild disabilities